Effects of tuber size and NPK 15-15-15 fertilizer rates on the performance of tigernut (Cyperus esculentus L) in Southwestern Nigeria - Olatinwo, G.O.; Olabode, O. S.; Kolawole, G. O. (ADAN JOURNAL OF AGRICULTURE, 2026)
Tigernut (Cyperus esculentus L.) is a highly nutritious and economically valuable crop with diverse food and industrial uses. Despite its growing demand in Nigeria, there is inadequate research on the appropriate size of the planting propagule and fertilizer requirements. Therefore, the performance of tigernut was evaluated at the Teaching and Research Farm, Ajayi Crowther University, Oyo, in 2025 in response to the size of the tuber planted and NPK 15:15:15 mineral fertilizer rates. Two pot experiments were laid out in Completely Randomized Design with three replications. The first assessed the influence of tuber sizes (Big (0.89 g), Medium (0.52 g), and Small (0.32 g)) and the second evaluated the response of tiger nut to NPK 15:15:15 fertilizer rates (0, 150, 300, and 450 kg/ha). Data were collected on sprouting, plant height, number of tillers, growth vigor, number and weight of tubers. Data were subjected to Analysis of Variance, and treatment means were separated by Duncan’s Multiple Range Test at 5% probability level. Tuber size had no significant effect on sprouting but significantly (p≤0.005) influenced plant height, vigor, and yield. Big-sized tubers produced the tallest plants (69 cm), highest growth vigor (3.7), and highest tuber weight (48.5 g/pot), while small-sized tubers produced plants with the shortest height (46 cm), vigor (2.2) and tuber weight (24.8 g/pot). NPK fertilizer rates significantly influenced growth parameters, with 450 kg/ha NPK producing the tallest plants (86.1 cm), while 150 kg/ha produced the highest number of tubers (98) and weight (107 g/pot). The control produced the shortest plant (73.9 cm), and the least number of tubers (66.0). In conclusion, big-sized planting tubers and moderate fertilizer rate; 150 kg/ha NPK 15:15:15 were appropriate agronomic practices for optimal growth and yield of tigernut in the study area.